AMOR DEI INTELLECTUALIS. VERNUNFT-UND GOTTESLIEBE IN GIPFELSÄTZEN NEUZEITLIECHER SYS-TEMBILDUNGEN (SPINOZA, HEGEL, SCHELLING, FICHTE) - Janke, Wolfgang (Daimon Revista Internacional de Filosofia, 1994)
There is a remarcable fact concerning the history of modern philosophy. The axiom since Spinoza runs: Love («amor Dei intellectualis», «absolute Liebe», «Wille de Liebe») , not reason («Vernunft», «Geist», «Reflexion») ist the first principle, which unifies alls beings. The first divison of our inquiry explains this principle within of the systems from Spinoza to Schelling in a critical way. The second part resumes the same axiom amongs Fichte’s philosophy of religion and reintroduces it as the real principle of human speculation.